An Autotransferable g‐C3N4 Li+‐Modulating Layer toward Stable Lithium Anodes. Issue 27 (16th May 2019) - Guo, Yanpeng; Niu, Ping; Liu, Yayuan; Ouyang, Yan; Li, Dian; Zhai, Tianyou; Li, Huiqiao; Cui, Yi
Abstract: Commercial deployment of lithium anodes has been severely impeded by the poor battery safety, unsatisfying cycling lifespan, and efficiency. Recently, building artificial interfacial layers over a lithium anode was regarded as an effective strategy to stabilize the electrode. However, the fabrications reported so far have mostly been conducted directly upon lithium foil, often requiring stringent reaction conditions with indispensable inert environment protection and highly specialized reagents due to the high reactivity of metallic lithium. Besides, the uneven lithium‐ion flux across the lithium surface should be more powerfully tailored via mighty interfacial layer materials. Herein, g‐C3 N4 is employed as a Li + ‐modulating material and a brand‐new autotransferable strategy to fabricate this interfacial layer for Li anodes without any inert atmosphere protection and limitation of chemical regents is developed. The g‐C3 N4 film is filtrated on the separator in air using a common alcohol solution and then perfectly autotransferred to the lithium surface by electrolyte wetting during normal cell assembly. The abundant nitrogen species within g‐C3 N4 nanosheets can form transient LiN bonds to powerfully stabilize the lithium‐ion flux and thus enable a CE over 99% for 900 cycles and smooth deposition at high current densities and capacities, surpassing most previous works. Abstract : A brand‐new autotransferable strategy is developed to build a Li + ‐modulating interfacial layer for lithium‐metal anodes by employing graphene‐like carbon nitride (g‐C3 N4 ). The rich N‐species within the g‐C3 N4 layer can form transient LiN bonds at the interface to uniform Li + flux distribution, contributing to a stable deposition for 900 cycles with a CE over 99%.